Resilience in a pandemic: the case of community pots in Lima, Peru - Alcázar, Lorena (2022)
Due to the food crisis caused by the COVID-19 pandemic, community pots have made a comeback in Lima’s vulnerable areas, as an alternative mechanism to fight hunger. They have become a symbol of resilience and solidarity, as well as spaces where women can support each other and become empowered. In this context, community pots have captured the attention of the State, which has created policies aimed at supporting them. However, these public initiatives still present significant shortcomings.